Use of a commercial ELISA for the detection of measles‐specific immunoglobulin G (IgG) in dried blood spots collected from children living in low‐resource settings. Issue 9 (18th May 2015) - Colson, K.Ellicott; Potter, Alan; Conde‐Glez, Carlos; Hernandez, Bernardo; Ríos‐Zertuche, Diego; Zúñiga‐Brenes, Paola; Collaborators, SM2015; Iriarte, Emma; Mokdad, Ali H.
<x xml:space="preserve">Abstract</x> Seroepidemiological monitoring of population immunity to vaccine‐preventable diseases is critical to prevent future outbreaks. Dried blood spots (DBS), drops of capillary blood dried on filter paper, are an affordable, minimally invasive alternative to venipuncture for collecting blood in field settings. However, few proven methods exist to analyze DBS for the presence of protective antibodies. This study validates a novel technique for measuring measles‐specific immunoglobulin G (IgG) in capillary DBS using a commercial ELISA. The predictive performance of a new method for analyzing DBS was tested by comparing matched serum and DBS samples from 50 children. The accuracy, precision, and reliability of the procedure were evaluated, and the optimal cut points to classify positive and negative samples were determined. The method was then applied to 1, 588 DBS collected during a large survey of children in Mexico and Nicaragua. Measles‐specific IgG in serum samples were 62% negative, 10% equivocal, and 28% positive. In comparisons with matched serum, DBS results were 100% sensitive and 96 · 8% specific, and agreed in 46 of 50 (92%) cases. The inter‐assay and intra‐assay coefficients of variation from kit‐provided controls were greater than desired (24.8% and 8.4%, respectively). However, in predictive simulations the average misclassification was only 3.9%. Procedures were found to be acceptable to surveyors and participants. Analyzing DBS collected in low‐resources settings is a feasible and accurate means of measuring population immunity to measles and should be used to generate objective measures of health status and health system performance. J. Med. Virol. 87:1491–1499, 2015. © 2015 Wiley Periodicals, Inc.